Water footprint: part 2– FFB production for oil palm planted in Malaysia - Zulkifli Hashim (2020)
Water accounting across the production of fresh fruit bunch (FFB) in the oil palm’s life cycle is gaining momentum arising from the importance placed on the need to quantify water footprint (WF). This article quantifies the WF of FFB production from oil palms grown in some areas in Malaysia, from an inventory data gathered from 2009-2012. The WF methodology of Hoekstra et al. (2009) was applied for calculating WF of FFB production. The data for crop evapotranspiration (ET) of 5.5 mm per day (Roslan and Mohd Haniff, 2004) was used to calculate green and blue WF. The results showed that for oil palm, the FFB yield average of 25-year life span was 20.7 t ha-1 yr-1. The FFB production WF was 1166 m3 t-1 FFB (WFgreen, 1055; WFblue, 3.56; and WFgrey, 107 m3 t-1). The results showed that the green WF was higher than the grey or the blue WF as planting of oil palm in Malaysia is without irrigation. Oil palm requires a lot of green water (rain water), but when the amount of rain water is lower than ET, it becomes necessary to determine the water deficit of the soil in the oil palm-growing areas. This is to ensure that any shortcoming of water can be provided through irrigation.